The history of the preparation of the collected works of I.A. Bunin in the publishing house “Petropolis” (Based on correspondence) - Sergey N. Morozov (Литературный факт, 2017)
The article is devoted to the history of editing, preparation and publication of I.A. Bunin’s Collected Works in the publishing house “Petropolis”. Excerpts of the writer's correspondence with the official representative of the publishing house M.S. Kaplan are published. In accordance with the contract, Bunin’s Collected Works were to be published during 1934–1935. However, Bunin's cooperation with Petropolis became a permanent problem due to constant delays and incompetence of the editors.